Framing Analysis of #BoikotTrans7 News on Lirboyo Islamic Boarding School in the Xpose Uncensored Program Using the Pan and Kosicki Model - Siti Auliza; Anang Anas Azhar (IAIN Madura, 2026)
This study aims to analyze the #BoikotTrans7 content on social media, especially on the TikTok platform, as well as media framing in the news on the Xpose Uncensored program on Trans7, which features footage of activities at Islamic boarding schools. The type of research used is descriptive qualitative with content analysis methods and uses the framing theory model of Zhongdang Pan and Gerald M. Kosicki, which includes syntactic, script, thematic, and rhetorical structures. The research data was obtained from the Xpose Uncensored program broadcast and the content and public comments on the TikTok platform. The results show that first, the #BoikotTrans7 content on TikTok contains various posts that re-display clips of the broadcast and provide clarification on parts of the broadcast that are considered to not fully present the cultural context of Islamic boarding schools. Second, the framing analysis shows that the news in the broadcast tends to emphasize visual aspects rather than contextual explanations of the values of Islamic boarding school customs and traditions, thus giving rise to various interpretations among the public. This study demonstrates the importance of presenting balanced and contextual information in news related to religious institutions.